Adhesins in the virulence of opportunistic fungal pathogens of human. Issue 4 (2nd October 2021) - Kumari, Amrita; Tripathi, Ankita H.; Gautam, Poonam; Gahtori, Rekha; Pande, Amit; Singh, Yogendra; Madan, Taruna; Upadhyay, Santosh K.
ABSTRACT: Aspergillosis, candidiasis, and cryptococcosis are the most common cause of mycoses-related disease and death among immune-compromised patients. Adhesins are cell-surface exposed proteins or glycoproteins of pathogens that bind to the extracellular matrix (ECM) constituents or mucosal epithelial surfaces of the host cells. The forces of interaction between fungal adhesins and host tissues are accompanied by ligand binding, hydrophobic interactions and protein-protein aggregation. Adherence is the primary and critical step involved in the pathogenesis; however, there is limited information on fungal adhesins compared to that on the bacterial adhesins. Except a few studies based on screening of proteome for adhesin identification, majority are based on characterization of individual adhesins. Recently, based on their characteristic signatures, many putative novel fungal adhesins have been predicted using bioinformatics algorithms. Some of these novel adhesin candidates have been validated by in-vitro studies; though, most of them are yet to be characterised experimentally. Morphotype specific adhesin expression as well as tissue tropism are the crucial determinants for a successful adhesion process. This review presents a comprehensive overview of various studies on fungal adhesins and discusses the targetability of the adhesins and adherence phenomenon, for combating the fungal infection in a preventive or therapeutic mode.